You can’t always get what you want: the role of change goal importance, goal feasibility and momentary experiences for volitional personality development - Lücke, Anna J.; Quintus, Martin; Egloff, Boris; Wrzus, Cornelia (European journal of personality, 2021)
Most adults want to change aspects of their personality. However, previous studies have provided mixed evidence on whether such change goals can be successfully implemented, perhaps partly due to neglecting the goals’ importance and feasibility as well as the experience of trait-relevant situations and states. This study examined associations between change goals and changes in self-reported Big Five traits assessed four times across two years in an age-heterogeneous sample of 382 adults (255 younger adults, Mage = 21.6 years; 127 older adults, Mage = 67.8 years). We assessed trait-relevant momentary situations and states in multiple waves of daily diaries over the first year (M = 43.9 days). Perceived importance and feasibility of change goals were analysed as potentially moderating factors. Contrary to our hypotheses, the results demonstrated that neither change goals nor goal importance or feasibility were consistently associated with trait change, likely due to inconsistent associations with momentary situations and behaviours. The results suggest that wanting to change one’s traits does not necessarily lead to changes without engaging in trait-relevant situations and behaviours. These findings provide novel insights into the boundary conditions of volitional personality development.